The future ingredients of our cities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Growing cities, growing food. Urban agriculture on the policy agenda A Reader on Urban Agriculture ACPA, BMZ, CTA, ETC, DSE/ZEL, SIDA, 2000. 543pp, ISBN 3 934068 25 1 CTA number 984. 40 credit points